2020
DOI: 10.1088/1757-899x/961/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Durability Study of Jute Fiber Reinforced Concrete

Abstract: Natural material/fiber should be used in the construction industry as it finds low cost and improve the properties of the material. Jute fiber is used in research study and carried out an experimental investigation on the mechanical properties of the jute fiber reinforced concrete (JFRC). Natural available jute fiber was chopped to the desired length and it was mixed in concrete to produce JFRC. The chopped jute fiber added in three different percentages i.e. 0.5%, 1.0%, & 1.5% in three various concrete mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Jute fibre inclusion increases the M25 compressive strengths of concrete. The ultimate compressive strength in concrete of grade M25 was attained at a 1.5% addition of jute fibre, at 19.7%, 9.7%, and 8.1%, respectively [9]. Addition of 0.5% jute fibre to concrete had a negative effect on its fresh characteristics.…”
Section: Introductionmentioning
confidence: 93%
“…Jute fibre inclusion increases the M25 compressive strengths of concrete. The ultimate compressive strength in concrete of grade M25 was attained at a 1.5% addition of jute fibre, at 19.7%, 9.7%, and 8.1%, respectively [9]. Addition of 0.5% jute fibre to concrete had a negative effect on its fresh characteristics.…”
Section: Introductionmentioning
confidence: 93%
“…Then, the bers were cut to pieces of the required size (15 mm), and the required amount of ber for the corresponding level of ber content was prepared. A ber length of 15 mm was adopted from previous studies for optimal performance [21], [22]. Subsequently, the required amount of burlap ber was mixed with ne and coarse aggregates and then poured into the mixer for 2 min by dry mixing with cement to ensure uniform distribution of ber.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In addition, research 55 found that NaOH treatment changed the structure of cellulosic fibers. Water molecules Reference Zhang et al 45 Tiwari et al 51 Naik et al 44 Mekala et al 52 Kshatriya et al 53 Specific gravity [kg/m 3 ] -1460 ---Specific modulus (GPa-cm 3 Zhang et al 45 Tiwari et al 51 Naik et al 44 Mekala et al 52 Kshatriya et al 53 cover a vast number of gaps in the amorphous area of cellulosic fibers, which are composed mostly of cellulose. Hydroxyl (OH) groups are sensitive to alkali, and the hydroxyl groups in this compound were broken down in the presence of alkali.…”
Section: Treatmentsmentioning
confidence: 99%